A daily-level, within-person examination of emotion regulation as a mediator of the relationship between sleep and behavior in youth - Feghali, Paulina T.; Iwamoto, Brooke K.; Triplett, Olivia M.; Rockwood, Nicholas J.; Nelson, Timothy D.; Van Dyk, Tori R. (Frontiers in Sleep, 2023)
Objective: Youth who experience behavioral and emotional problems are at risk for sleep disturbance, while sleep disturbance also perpetuates behavioral and emotional problems. While the relationship between sleep and psychopathology in clinical mental health samples is well-established, exploration of the underlying mechanisms maintaining this relationship is limited. The purpose of this study is to explore within-person variability in emotion regulation as a mechanism of the relationship between sleep and psychopathology in a clinical youth sample. Methods: Using a within-person design, 25 children (ages 6-11; 64% male; 44% non-Hispanic White) presenting to outpatient behavioral health treatment with mental health concerns were recruited to participate in a 14-day study. Daily reports of objective sleep duration via actigraphy, self-reported subjective sleepiness, and parent-reported internalizing and externalizing problems and emotion regulation were collected. Multilevel mediation analyses were used to examine the mediating effect of emotion regulation on the daily-level relationship between sleep and behavior problems. Results: At the within-person level, emotion dysregulation was a significant mediator of the relationships between objective sleep duration and both externalizing (MCCI [.0005 – .0063]) and internalizing problems (MCCI [.0001 –.0025]). Contrary to hypotheses, when youth slept more than usual, internalizing and externalizing problems were worse through the indirect effect of increased emotion dysregulation. Conclusions: Inconsistencies in schedules and routines, even if in a positive direction, may have short-term negative consequences for youth with emotional and behavioral concerns. Future research should look to address sleep variability and how deviations in routine may impact behavior more broadly, through the indirect effects of emotion regulation.